Artificial regression based mis-specification tests for discrete choice models - Murphy, Anthony (Economic & Social Studies, 1994)
Lagrange Multiplier (LM) tests for omitted variables, neglected heteroscedasticity and other mis-specifications in general discrete choice models may be simply and conveniently calculated using an artificial regression. This artificial regression approach is likely to have better small sample properties than the more common outer product gradient (OPG) form of LM test.
Keywords: Artifical regressions; Discrete choice models; Statistical methods